Permanganate Oxidation of 2.Aminobutyric Acid: Kinetics, Mechanism and Salt Effect. - PRAKASHAN, V.C.; VARGHESE, GIJU; THAPLlYAL, N.K.; TIWARI, P.N. (Asian Journal of Chemistry, 2010)
The permanganate oxidation of 2-aminobutyric acid (2-ABA) has been studied iodometrically in sulphuric acid media. The reaction follows first order kinetics with respect to oxidant and reductant. Zücker-Hammet's and Bunnett's hypotheses were tested and it has been found that the reaction is acid catalysed and water molecules act as a proton abstracting agent in the rate determining step. The effect of various cations and anions on reaction velocity was studied. No primary salt effect was observed. Various activation parameters have been computed.